Evaluating the student's entrepreneurial intention: role of prosocial motivation, social entrepreneurial attitude, and psychological capital among millennials / Suvidha Khanna, Sangeeta Chauhan and Sheetal Bhagat - Khanna, Suvidha; Chauhan, Sangeeta; Bhagat, Sheetal (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The purpose of this study is to investigate impact of prosocial motivation on psychological capital and social entrepreneurial attitude furthermore its aims to evaluate the impact of psychological capital and social entrepreneurial attitude on social entrepreneurial intention and finally the study examines the impact of prosocial motivation on social entrepreneurial intention. A questionnaire survey was conducted in the northern indian region covering Jammu &Kashmir, Uttrakhand and Himachal Pradesh. Data were collected from 368 respondents whoare pursuing postgraduate (PG) and undergraduate (UG) studies in tourism. SmartPLS 4 is utilized for the data analysis.Results offer empirical support for the hypotheses that prosocial motivation positively impact psychological capital and social entrepreneurial attitude and also show the positive impact of social entrepreneurial attitude and psychological capital on social entrepreneurial intention. The study highlight that there is a significant relation between prosocial motivation and SEI.The findings of this study extend existing views on the positive relationship between Prosocial Motivation, psychological capital, social entrepreneurial attitude in the social entrepreneurship research field by focusing on the perspective of SEI. In particular, this study reveals the complex process of how prosocial motivation and other factors impact SEI, which has rarely been explored in the extant literature